Medication Errors in Anesthesiology: Is It Time to Train by Example? Vignettes Can Assess Error Awareness, Assessment of Harm, Disclosure, and Reporting Practices. Issue 1 (January 2022) - Duffy, Caoimhe C.; Bass, Gary A.; Duncan, James; Lyons, Barry; O'Dea, Angela
Abstract : Background: Perioperative medication errors (MEs) are complex, multifactorial, and a significant source of in-hospital patient morbidity. Anesthesiologists' awareness of error and the potential for harm is not well understood, nor is their attitude to reporting and disclosure. Anesthesiologists are not routinely exposed to medication safety training. Methods: Ten clinical vignettes, describing an ME or a near miss, were developed using eDelphi consensus. An online survey instrument presented these vignettes to anesthesiologists along with a series of questions assessing error awareness, potential harm severity, the likelihood of reporting, and the likelihood of open disclosure to the patient. The study also explored the influence of prior medication safety training. Results: Eighty-nine anesthesiologists from 14 hospitals across Ireland (53.9% were residents, and 46.1% were attendings) completed the survey. Just 35.6% of anesthesiologists recalled having had medication safety training, more commonly among residents than attendings, although this failed to reach significance ( P < 0.081). Medication error awareness varied with the vignette presented. Harm severity assessment was positively associated with error awareness. The likelihood of patient disclosure and incident reporting was both low and independent of harm severity assessment. Conclusions: Perioperative ME awareness and assessment of potential harm by anesthesiologists is variable. Self-reported rates of incident reporting and error disclosure fall short of the standards that might apply in an environment focused on candor and safety. An extensive education program is required to raise awareness of error and embed appropriate reporting and disclosure behaviors. Vignettes, designed by consensus, may be valuable in the delivery of such a curriculum. Abstract : Supplemental digital content is available in the text.